(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Virtual reality is an interactive three-dimensional artificial world, immersion in which creates the illusion of reality for the user. It not only affects the human senses, but also itself reacts to its movements and actions. Initially, a new discovery in the world of information technology was used exclusively for entertainment purposes: virtual reality glasses and helmets were created, allowing you to plunge into your favorite game with a head and feel like the main character. However, over time, virtual reality began to conquer other areas of human life: medicine, architecture, cinema, art, education, etc. This article describes how virtual reality can be incorporated into the educational process and how it can affect students’ mastery of the material, identifies the pros and cons of using this technology when learning, and also examines modern VR devices and educational programs.